TUJUAN ATURAN POLIGAMI DALAM UNDANG-UNDANG NO. 1 TAHUN 1974 TENTANG PERKAWINAN - Khiyaroh, Khiyaroh (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2025)
This study discusses the rules of polygamy in the rules of Law No. 1 of 1974 concerning Marriage. The focus of the study in writing is about the reasons, objectives and the level of achievement of the rules of polygamy after being passed and enforced in Indonesia. Polygamy is an issue that has always been debated from time to time. Polygamy in Indonesia has been carried out since before Indonesia's independence. This is due to the absence of explicit rules governing marriage in Indonesia. Polygamy which is carried out arbitrarily makes women's rights discriminated and leaves children and wives neglected. This paper is a normative legal writing with the approach used, namely the historical approach to find out the historical values that are the background of the formation of the marriage law rules. So that by knowing the background or reasons for making rules about polygamy is expected to minimize the cases that occur in the family and one of them is polygamy. This paper uses the theory of legal protection with the aim of answering the formulation of the problem in the form of the objective of the existence of polygamy rules. With the existence of regulations on polygamy in the Marriage Law it is expected to improve the status of women by protecting the rights of wives in the family. In addition to emphasizing the rules of polygamy so that polygamy is not carried out arbitrarily.